High performance parallelism pearls : multicore and many-core programming approaches - Reinders, James; Jeffers, Jim (Morgan Kaufmann/Elsevier, 2015)
This book shows how to leverage parallelism on processors and coprocessors with the same programming - illustrating the most effective ways to better tap the computational potential of systems with Intel Xeon Phi coprocessors and Intel Xeon processors or other multicore processors. It includes examples of successful programming efforts, drawn from across industries and domains such as chemistry, engineering, and environmental science. Each chapter in this edited work includes detailed explanations of the programming techniques used, while showing high performance results on both Intel Xeon Phi coprocessors and multicore processors. Dozens of new examples and case studies illustrate "success stories" demonstrating not just the features of these powerful systems, but also how to leverage parallelism across these heterogeneous systems. --